The Influence of E-Service Quality, and Customer Satisfaction On Go-Send Customer Loyalty In Surabaya - Wirapraja, Alexander; Aribowo, Handy; Setyoadi, Eddy Triswanto (Indonesian Journal of Information Systems, 2021)
The shipping industry is currently one of the vital aspects of industrial business, especially in the current Covid-19 pandemic era. Delivery of goods, both products and foodstuffs, can be done quickly by using courier services that can be accessed through online media such as personal gadgets, namely computers and smartphones. One of the features of GO-Jek Indonesia is a courier service called Go-Send, the problem that arises is that there is competition in the same line of business, causing consumers to have many choices when making deliveries. Measuring the level of loyalty makes researchers interested in measuring Go-Send users' perceptions of the level of customer loyalty as measured by e-service quality and customer satisfaction. This study used a quantitative method using a questionnaire with a Likert scale measurement and a sample of 109 respondents was obtained which was then measured using the Structural-Equation-Modeling (SEM) method with a 95% confidence level. The results of this study indicate that Go-Send user loyalty is positively and significantly influenced by customer satisfaction and the level of e-service quality.